An experimental and numerical study on the in-plane axial and shear behavior of sprayed in-situ concrete sandwich panels. (1st April 2021) - Serpilli, M.; Clementi, F.; Lenci, S.
Highlights: Sprayed in-situ RC sandwich panels offer facilitations in mounting and construction processes. The in-plane axial and shear behaviors are characterized by laboratory experimental test. The 3D FEM model takes into account the insulation layer, steel connectors and material nonlinearities. Abstract: The paper deals with the experimental and numerical characterization of the in-plane axial and shear mechanical behavior of sprayed in-situ reinforced concrete (RC) sandwich panels, used as structural walls. Axial compression tests were carried out on specimens with different slenderness ratios to study their behavior under axial vertical loads. While the diagonal compression test and shear load with constant compression test were respectively performed on squared panels, analyzing their response to in-plane horizontal lateral forces. Ultimate axial and shear loads have been experimentally determined and the most significant load–displacement diagrams have been reported. The obtained results have been compared with other experimental campaigns on RC sandwich panels and with conventional RC walls equations, available in codes of practice and literature. The structural potentialities of RC sandwich panels as load-bearing and shear walls are highlighted. The experimental investigation is corroborated by a 3D nonlinear finite element (FE) numerical analysis, considering the influence of the insulation layer, the efficiency of steel connectors, and the involved material nonlinearities.